Faith-Based Organizations in Development Discourses and Practice (Taylor & Francis, 2025)
Exploring faith-based organizations (FBOs) in current developmental discourses and practice, this book presents a selection of empirical in-depth case-studies of Christian FBOs and assesses the vital role credited to FBOs in current discourses on development. Examining the engagement of FBOs with contemporary politics of development, the contributions stress the agency of FBOs in diverse contexts of development policy, both local and global. It is emphasised that FBOs constitute boundary agents and developmental entrepreneurs: they move between different discursive fields such as national and international development discourses, theological discourses, and their specific religious constituencies. By combining influxes from these different contexts, FBOs generate unique perspectives on development: they express alternative views on development and stress particular approaches anchored in their theological social ethics. This book should be of interest to those researching FBOs and their interaction with international organizations, and to scholars working in the broader areas of religion and politics and politics and development.